Le Bruit de l'amer: Time, Loss and Fossilized Romanticism in Madame Bovary - Luke Bouvier (Flaubert: Revue Critique et Génétique)
Recent studies have focused on Emma Bovary's “temporal disorder”, her strange inability to produce an event in her life or to integrate time into her experience. A key scene in this regard is Emma's odd failure to mourn her mother as she acts out a set of elaborate romantic grief rituals that ultimately leave her bored and unmoved. Drawing on a broadly psychoanalytic framework, and in particular recent work on trauma and addiction, this study suggests that this scene is symptomatic of a broader inability to assimilate loss, which manifests itself in the problems of boredom and addiction, and in Emma's general inability to orient herself temporally with respect to the past. Of particular importance are the linguistic implications of this problem, the way in which such a temporal disorder linked to a failure of mourning can be read precisely through the disturbances of language that it provokes. In the odd, inscrutable figure of la mère Rollet, for example, one can discern the cryptic adventure of language that arises from the problem of unassimilated loss in this novel, the very conspiracy of words that drives Emma to suicide through the staging of equivocal, uncanny returns.  Ultimately, if Emma's failure to mourn her mother reveals a certain inability to mourn time itself, this scene unmistakably depicts Emma's inability or refusal to mourn a dead aesthetic as well. Indeed, when Emma indulges her taste for romantic imagery in listening to “les chants de cygnes mourants”, what she fails to hear is precisely the clichéd, worn-out nature of such imagery, romanticism's equivocal double voicing as a champ de signes mourants.